The Effectiveness of Preoperative Nursing Visitation in Reducing the Level of Preoperative Anxiety and Postoperative Pain in Elective Surgery Patients: A Systematic Literature Review - Jatmiko, Agus (Universitas STRADA Indonesia, 2023)
Preoperative nursing visitation is a method used to prepare the patient's knowledge and psychology for surgery, in order to prevent preoperative anxiety and decrease postoperative pain as well as have a positive impact on the smooth running of the surgical process. The purpose of this research is to provide evidence regarding the effectiveness of preoperative nursing visitation in reducing preoperative anxiety and postoperative pain. This research use PubMed, Wiley Online Library, Cochrane Online Library, ProQuest, and Science Direct were investigated for experimental design studies on the effect of preoperative nursing visitation in reducing postoperative anxiety and pain in elective surgery patients. Three studies were identified and analyzed from 104 initial articles. Data were then extracted from the study and summarized descriptively. The conclusion Preoperative nursing visits can reduce anxiety levels and postoperative complications, especially postoperative pain and are highly recommended as a nursing protocol in routine care for surgical patients.